Environmental factors and the water regime of De Hoop Vlei - Butcher, Shirley Elizabeth (Department of Environmental and Geographical Science, 2023)
The De Hoop Vlei is an internationally registered wetland of great ecological richness which is situated partly within the first and largest nature reserve established by the Cape Department of Nature and Environmental Conservation. This vlei has flooded twice and been dry on four occasions this century. There has been speculation that land management practices in the catchment are the cause of such extremes. This claim is investigated with reference to established techniques for modelling runoff from rainfall data. As background to the study the characteristics of the De Hoop catchment have been documented. This information was not previously available and provides an essential basis for further study of conditions in De Hoop Vlei. It is found that whilst large differences in runoff may occur in localised areas due to changing land management practices, because of the composite hydraulic characteristics of the entire catchment it is not possible at the present time to provide a final answer to the question of whether stream to De Hoop has changed significantly due to human impact. Nevertheless, some important environmental changes affecting basin capacity and biological factors at De Hoop have been elucidated by this study.